An Initiative to Develop OER-Based General Education Courses in Higher Education - Shanta Goswami Varma; Xinyue Ren (Open Praxis)
Following the institution’s strategic goal to make it an affordable campus, institutional administrators advocated using open educational resources (OERs) to reduce the cost of attendance and improve low retention rates in gateway courses. In this project, researchers invited faculty members to systematically design, develop, and deliver three general education (GED) courses with OERs to promote and test innovative pedagogical approaches for student success and retention. The project also aims to enable students to complete and earn their degrees seamlessly and affordably. The purpose of this paper is to describe the initiative, disseminate information to instructors, administrators, and other scholars on the effective practices to integrate OERs into GED courses, and show the effectiveness of OERs in increasing students’ learning experiences, instructors’ teaching experiences, and student retention.